Niepełnoletni rodzice i ich rodziny jako podmiot wsparcia. Badania własne - Ratajczak, Łukasz P. (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
Underage parenting is an experience that can be defined as difficult, even critical. It is the same both for teenagers and their families. Adopting the role of a father and mother in adolescence, and so prematurely, generates a number of difficulties that occur in almost every sphere of functioning of these young people. It is therefore necessary to take steps supporting not only underage parents, but also their families. In this article, the issue of supporting teen parents and their families have been described. The sources of information are the empirical studies of underage mothers carried out in 2008 and underage fathers in 2012-2013. They enabled not only to recognize the difficulties that usually involve teen parents, but also the scope and type of support they receive.
Underage Parents and Their Families as a Subject of Support. Independent Research
Keywords: social support; teenage parents; support: informational; instrumental; emotional